Kajian Keberlanjutan Sosial Ekonomi pada Destinasi Wisata Pos Lintas Batas Negara Skouw - Grace Friscilia Thane; Novi Sunu Sri Giriwati; Sri Utami Aziz; Susilo Kusdiwanggo (Universitas Sebelas Maret Surakarta, 2023)
The Skouw PLBN needs to address and develop a number of things in order to draw more tourists, including local cuisine, cultural arts facilities, and sports facilities. To find out the urgency, an assessment was carried out with the parameters of the SDGs with three main pillars, namely the balance between aspects of the economic, social and environmental fields. Field observations and literature studies served as the data collection method. The global action plan's SDGs implementation is based on the 5 P principles (People, Planet, Prosperity, Peace, and Partnership). The 4 Ps must be examined for the SDGs' accomplishment in order to understand social and economic problems in society. The outcomes include a number of strategies on the topics of food accessibility and availability, healthy living, education, gender equality, as well as community involvement to collaborate with the government to develop the Skouw PLBN region in a social and economic sustainable manner.